Antioxidant Intervention Attenuates Aging-Related Changes in the Murine Ovary and Oocyte - Mandy G. Katz-Jaffe; Sydney L. Lane; Jason C. Parks; Blair R. McCallie; Rachel Makloski; William B. Schoolcraft (Life, 2020)
Advanced maternal age (AMA) is associated with reduced fertility due in part to diminished ovarian follicle quantity, inferior oocyte quality, chromosome aneuploidy, and lower implantation rates. Ovarian aging is accompanied by increased oxidative stress and blunted antioxidant signaling, such that antioxidant intervention could improve reproductive potential. The first aim of this study was to determine the molecular effects of antioxidant intervention in the ovaries and oocytes of aged mice, utilizing a supplement containing only naturally occurring açaí (Euterpe oleracea) with an oxygen radical absorbance capacity of 208,628 μmol Trolox equivalent (TE)/100 g indicating high antioxidant activity. Nine month old female CF-1 mice were administered 80 mg/day antioxidants (n = 12) or standard diet (n = 12) for 12 weeks. In the ovary, antioxidant treatment upregulated β-adrenergic signaling, downregulated apoptosis and proinflammatory signaling, and variably affected cell growth and antioxidant pathways (p < 0.05). Exogenous antioxidants also increased the oocyte expression of antioxidant genes GPX1, SOD2, and GSR (p < 0.05). A feasibility analysis was then conducted on female AMA infertility patients as a proof-of-principle investigation. Patients (n = 121; <45 years old) consented to receiving 600 mg antioxidants three times daily for ≥8 weeks preceding infertility treatment. Preliminary results indicate promising outcomes for AMA patients, warranting further investigation.